2015
DOI: 10.1007/s10071-015-0919-4
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation in wild Barbary macaques: factors affecting free partner choice

Abstract: A key aspect of cooperation is partner choice: choosing the best available partner improves the chances of a successful cooperative interaction and decreases the likelihood of being exploited.However, in studies on cooperation subjects are rarely allowed to freely choose their partners.Group-living animals live in a complex social environment where they can choose among several social partners differing in, for example, sex, age, temperament, or dominance status.Our study investigated whether wild Barbary maca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 69 publications
(104 reference statements)
4
53
3
1
Order By: Relevance
“…Furthermore, the closeness of the rank between individuals was also related to higher cooperation success, similarly to results from chimpanzees (46) and hyenas (47) [although studies in other species found the opposite effect, with higher cooperative success being related to increased rank distance between partners (30,34)]. In the Two-apparatus condition, the coordination between partners is particularly important; therefore, it is possible that animals closer in rank paid closer attention to one another compared with partners in dyads with larger rank distances.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Furthermore, the closeness of the rank between individuals was also related to higher cooperation success, similarly to results from chimpanzees (46) and hyenas (47) [although studies in other species found the opposite effect, with higher cooperative success being related to increased rank distance between partners (30,34)]. In the Two-apparatus condition, the coordination between partners is particularly important; therefore, it is possible that animals closer in rank paid closer attention to one another compared with partners in dyads with larger rank distances.…”
Section: Discussionsupporting
confidence: 56%
“…However, if only one end of the string is pulled, the other end becomes inaccessible and the tray cannot be moved forward anymore, rendering the trial unsuccessful. This task has been used with a wide range of species, from ravens to elephants [chimpanzees (27)(28)(29), macaques (30), elephants (31), gray parrots (32), rooks (33), ravens (34), kea (35,36), and dogs (37)], with many succeeding in solving the task after being initially trained individually to pull the tray out by pulling both ends of the rope together.…”
mentioning
confidence: 99%
“…With the possible exception of playback experiments (e.g. [87]), there are virtually no field experiments on mindreading or cooperation in non-human primates comparable to those conducted in the laboratory (see [31,88] for exceptions). This state of affairs is perhaps likely to change in the coming years since field experiments on social problems (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In the loose string pulling paradigm, tolerance (i.e., co-feeding and food sharing rates) was also an important predictor of success in chimpanzees (Melis et al, 2006c) and wild Barbary macaques, Macaca sylvanus (Molesti and Majolo, 2016). In a recent study, chimpanzees were more likely to choose a risky social option (success depended on the partner's 38 willingness to reciprocate) when paired with a close bonding partner compared to another group member not closely bonded with the subject (Engelmann and Herrmann, 2016).…”
Section: Factors Affecting Prosocial Tendencies: Kinship Dominance mentioning
confidence: 95%
“…Mutualism has been shown in many primate species, including chimpanzees (e.g., Chalmeau, 1994;Crawford, 1937;Hirata and Fuwa, 2007;Melis et al, 2006b, c;Melis and Tomasello, 2013;Suchak et al, 2014), bonobos, Pan paniscus , orang-utans (Chalmeau et al, 1997a;Völter et al, 2015), brown capuchin monkeys (Brosnan et al, 2006;Chalmeau et al, 1997b;de Waal and Davis, 2003;Hattori et al, 2005;Visalberghi et al, 2000), cottontop tamarins, Saguinus oedipus (Cronin et al, 2005;Cronin and Snowdon, 2008), and different macaque species, Macaca tonkeana, M. mulatta, M. sylvanus (Molesti and Majolo, 2016;Petit et al, 1992).…”
Section: Mutualismmentioning
confidence: 97%